Hyperosmolar blood–brain barrier opening using intra-arterial injection of hyperosmotic mannitol in mice under real-time MRI guidance - Chu, Chengyan; Jablonska, Anna; Gao, Yue; Lan, Xiaoyan; Lesniak, Wojciech G.; Liang, Yajie; Liu, Guanshu; Li, Shen; Magnus, Tim; Pearl, Monica; Janowski, Miroslaw; Walczak, Piotr (Nature protocols, 2022)
The blood–brain barrier (BBB) is the main obstacle to the effective delivery of therapeutic agents to the brain, compromising treatment efficacy for a variety of neurological disorders. Intra-arterial (IA) injection of hyperosmotic mannitol has been used to permeabilize the BBB and improve parenchymal entry of therapeutic agents following IA delivery in preclinical and clinical studies. However, the reproducibility of IA BBB manipulation is low and therapeutic outcomes are variable. We demonstrated that this variability could be highly reduced or eliminated when the procedure of osmotic BBB opening is performed under the guidance of interventional MRI. Studies have reported the utility and applicability of this technique in several species. Here we describe a protocol to open the BBB by IA injection of hyperosmotic mannitol under the guidance of MRI in mice. The procedures (from preoperative preparation to postoperative care) can be completed within ~1.5 h, and the skill level required is on par with the induction of middle cerebral artery occlusion in small animals. This MRI-guided BBB opening technique in mice can be utilized to study the biology of the BBB and improve the delivery of various therapeutic agents to the brain. This protocol describes a method for blood–brain barrier opening (BBBO) under the guidance of interventional MRI in mice. The method, which considerably reduces BBBO variability, can be used to improve delivery of therapeutics to the brain.